HVAC System Design by Using Geothermal Heat Pump - Hamza Mohamed; Abdallah Algoud (AlQalam Journal of Medical and Applied Sciences, 2025)
A design of a geothermal heat pump heating, ventilating, and air conditioning system has been done for XYZ Indianapolis School by using renewable energy. Geothermal energy is one of the important energies that has proved itself in air conditioning systems all over the world. The design was classified in three points as follows. Using borehole heat exchanger (BHEs) vertical type, heat pump and all its equipment such as mechanical room, pipes, and fitting design to cover the total load of the school the results were 20 boreholes and a total flow rate of 60 gpm (3 gpm/bore) of 20 % propylene solution, and spacing 20 ft with 1.1 Hp and 6.5 in impeller size. For individual borehole design, the results were 15 boreholes and a total power consumption 1.1 kW. For the ventilation design, the peak load for heating is 42779 Btu/hr, and for cooling, it is 47779 Btu/hr. There are 4 boreholes, a 0.5 hp electric pump with a flow rate of 10 gpm a 40ft of H2O pressure drop, and a 10 hp fan integrated with a water-to-water heat pump. The total load we assumed for the heating supply in class 6 and the corridor are 10% and 25 %, respectively. The thermal resistance was calculated for each case according to the fluid flow rate. The ventilation load of the school is designed separately from the heating and cooling loads and connected to a water-water heat pump that will make the system work with high efficiency. Finally, we designed this project using Geothermal Energy, which is cleaner than conventional energy.